An approach to the notion of relation to knowledge, revised in the light of Lacan’s theory of the subject, to be applied in the investigation of the production processes of visual art in university students - Pastorino, Magalí (2022)
The notion of relationship with knowledge is valid in the field of research in education and as a dense notion it places us in the question of the subject and knowledge. In the way of Beillerot, this notion involves a unique creative process, which is why it is relevant for university artistic teaching in visual art and its deepening updates the field of studies of productive processes. However, the notion originates from a phrase in Lacanian work from the 1960s. In the light of this work, we propose to shed light on the scope of the notion to apply in the investigation of the productive processes of advanced university students of visual art. In this way we integrate the unconscious formations to the field of university artistic teaching in visual art.